Borrelia bugdorferi genospecies in humans and ticks in the Alpe Adria region - Cinco, M... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
In this paper we report on the genospecies prevalence of Borrelia burgdorferi sensu stricto we found in human Lyme borreliosis and in the tick vector Ixodesricinus in two distinct but restricted areas of the Alpe Adria region, the Karst and Belluno territory. Different rates of genospecies prevalence were found in the two areas studied, in humans as well as in ticks, with a netpredominance of Borrelia afzelii in human infection in the Belluno area.
Keywords: Borrelia burgdorferi; Isolation and purification; Ixodes; Lyme disease; Lymska bolezen sin Lymska borelioza